Effect of Warm and Cold Compress Applications on Joint Pain Scale in Elderly Patients with Rheumatism - Aisyaturrodliyah, Auliya; Sari, Nova Nurwinda; Oktalina, Riska (Genius Journal, 2026)
Introduction : Rheumatism is a degenerative disease commonly experienced by the elderly and is characterized by chronic joint pain that can interfere with daily activities. Pain in rheumatism sufferers often fluctuates, necessitating simple, safe, and effective non-pharmacological interventions to help reduce pain levels. Warm and cold compresses are simple therapies frequently used in nursing practice to reduce pain and improve patient comfort. However, the effectiveness of these two methods in reducing pain levels still requires scientific proof Objective:. It is known that there is a difference between warm compresses and cold compresses on the scale of joint pain in elderly rheumatism sufferers at the UPTD of the Tresna Werdha Natar Elderly Social Home, South Lampung, Lampung Province in 2025. Method: This study used a quasi-experimental design with a two-group pretest-posttest approach. The study sample consisted of elderly patients with rheumatism, divided into two groups: a warm compress group and a cold compress group. Pain scale measurements were conducted before and after the intervention using a Numeric Rating Scale (NRS). Data analysis was performed using nonparametric tests, namely the Wilcoxon test to determine differences before and after the intervention, and the Mann-Whitney test to compare differences between the two groups. Result The results of the study showed that both warm and cold compresses were effective in reducing pain scales in elderly rheumatic patients with a mean value of 1.27 ± 0.704 for warm compresses. The mean value for cold compresses was 1.60 ± 0.632. There was a decrease in the average pain scale after the intervention in both groups. However, the Mann-Whitney test results showed no significant difference between the two interventions with a p-value of 0.058. Conclusion: Therefore, both can be recommended as non-pharmacological therapies in the management of rheumatic pain in the elderly